1995
DOI: 10.1095/biolreprod52.6.1274
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Tenr, an RNA-Binding Protein, in a Lattice-Like Network within the Spermatid Nucleus in the Mouse1

Abstract: In a molecular screen for cDNAs that encode protamine RNA-binding proteins, we obtained seven independent clones that encode Tenr, a testis nuclear RNA-binding protein. Tenr is a 72-kDa protein that has one copy of a previously described RNA-binding domain. Northwestern blotting experiments showed that a maltose-binding protein-Tenr fusion binds to a variety of RNAs in vitro and that it does not bind to single-stranded or double-stranded DNA. The Tenr gene is transcribed exclusively in the testis, and its mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 54 publications
(57 reference statements)
1
55
1
Order By: Relevance
“…The C terminus of K88 included a 380-aa region (Fig. 1B) that has extensive homology with the entire predicted C. elegans T20H4.4 gene product (37% identity, 63% similarity), the S. cerevisiae HRA400 gene product (23% identity, 49% similarity), and the C terminus of the murine Tenr protein (29% identity, 51% similarity), three proteins of unknown function (60,72). The sequence obtained for the human K88 cDNA showed near identity with the sequences reported for the dsRNA-specific AdDs from human (33,48) and rat (48) cells.…”
Section: Resultsmentioning
confidence: 99%
“…The C terminus of K88 included a 380-aa region (Fig. 1B) that has extensive homology with the entire predicted C. elegans T20H4.4 gene product (37% identity, 63% similarity), the S. cerevisiae HRA400 gene product (23% identity, 49% similarity), and the C terminus of the murine Tenr protein (29% identity, 51% similarity), three proteins of unknown function (60,72). The sequence obtained for the human K88 cDNA showed near identity with the sequences reported for the dsRNA-specific AdDs from human (33,48) and rat (48) cells.…”
Section: Resultsmentioning
confidence: 99%
“…Immunocytohistochemical experiments on adult mouse male testes with the ILF3 antiserum detect expression of the protein in spermatocytes and early haploid spermatids, cells that do not express the Prm1 gene (unpublished data). Additionally, four of the five cDNAs identified in this expression cloning screen encode proteins that contain the dsRBM, a motif that binds double-stranded RNA or single-stranded RNA with structure (Lee et al 1996;Schumacher et al 1995aSchumacher et al , 1995b. While the Prm1 3ЈUTR does not contain any extensive regions that could form dsRNA, there are two alternate stem loops that could theoretically form (Lee et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Schumacher et al has shown that this protein is localized to round and early elongating spermatid cells and suggests that it may be involved in testis-specific nuclear posttranscriptional processes such as alternative splicing, hnRNA packaging, or transport of mRNAs (13). Thus, TENR may bind to substrates but not have the ability to edit them and may even act as an inhibitor of mRNA editing (14).…”
Section: Origin and Evolution Of Adarmentioning
confidence: 99%